(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Starbuck is the most leading coffee houses around the globe most especially here in Manila. Everyday, Filipinos start their day with a cup of coffee, it is like a traditional way of making their day lively as they are woken by every zip of coffee. Starbucks has been popular from before till now, it's because they have provided the best coffee and places for its customers whereas they are known for being a high-class coffee house and it is because of their coffee specialty and luxury vibrant store. Coffee’s preferences evolve from a simple way of brewing coffee to a complicated new version, same as for the ambiance of the place where they have innovated but still customers' needs are complex. So, in this study, the researchers have come up with the ideas to allocate the possible existing unsatisfied customer and to collect a basis for customer satisfaction. As for the results, the researchers found out that most customers of Starbucks at SM Fairview Branch are 18-25 years old, female, a student and single, and they are satisfied with the taste, service, ambiance, and presentation which defer to the price where most answered that they are not satisfied. The most encountered problem by customers is that the mall time opening and closing is too early, making it difficult for them to drink coffee in the morning. At the end of the research, the researchers found out that based on the results, Starbucks has always had a long line up at the counter, and some products are way too pricey and most of the respondents say that they are struggling to open and close it. Therefore, the researchers have come up with the idea to create an action steps or action plan to recommend improved customer satisfaction at Starbucks SM Fairview branch. The researchers plan to apply an online ordering system to lessen the line at the counter, collect data for other bases and information, and post a card outside or online for customers acceptance. Keywords: